Primary Health Care Services Utilization and Its Determinants in Rural Areas, Central Sudan - A Mohammed , Omer; Shaza Babikir; Salma Alrwa; Omer Abdelaziz A.Saeed; Mohamed Ishag Ahmed; Almothanna Zaki H.Ahmed (International Journal of Medical Students, 2025)
BACKGROUND: In 2022, the World Health Organization and Sudan’s transitional government developed a country cooperation strategy to move closer to universal health coverage (UHC) by enhancing access to quality primary health care (PHC). Evaluating PHC centers and identifying factors influencing their utilization is essential for improving these services. This study aimed to assess the perceptions of Om Shanig residents regarding PHC services at their rural hospital and to determine the factors affecting their usage. METHODS: This was a cross-sectional, community-based study conducted in Om Shanig, a rural area in Gezira State, from December 20-24, 2022. Data were collected from adults aged 18 years and older using a pretested, interviewer-administered questionnaire. The data were analyzed using SPSS version 23. RESULTS: A total of 95.7% of participants had visited the PHC center and were generally satisfied with most services. However, 21.7% reported poor sanitation, 42.2% noted the absence of radiologic services, and 23.8% found laboratory services to be only sometimes available. Additionally, 4.5% expressed an unwillingness to continue using the center. Key factors influencing the decision to utilize the center included waiting time (p = 0.013), availability of medications (p = 0.003), and satisfaction with diagnostic services, treatment, nursing care, administration, laboratory tests, doctors, and vaccinations (p < 0.001 for all). CONCLUSION: The overall utilization of primary healthcare services was good. However, it may decline due to issues such as the lack of medications and laboratory tests. Ensuring the availability of essential services and educating the community about what services to expect at each level is crucial for maximizing the potential of primary care.